(untitled) (Journal of Pathology of Nepal, 2023)
Gallbladder neuroendocrine carcinoma is a rare neoplasm thought to arise in the background of chronic inflammation triggered by cholelithiasis. The symptoms of this tumor overlap with those of cholecystitis and other carcinomas of the gall bladder. The imaging findings with fine needle aspiration cytology help in the pre-operative diagnosis. However, the gold standard for diagnosis is histopathology evaluation with immunohistochemistry. We report a case of a 76-year female who was clinically diagnosed with acute calculus cholelithiasis and underwent surgery. The histopathology and immunohistochemistry of the gallbladder revealed neuroendocrine carcinoma.